2014
DOI: 10.1371/journal.pone.0095474
|View full text |Cite
|
Sign up to set email alerts
|

Similar Metabolic Changes Induced by HIPVs Exposure as Herbivore in Ammopiptanthus mongolicus

Abstract: Herbivore-induced plant volatiles (HIPVs) are important compounds to prim neighboring undamaged plants; however, the mechanism for this priming process remains unclear. To reveal metabolic changes in plants exposed to HIPVs, metabolism of leaves and roots of Ammopiptanthus mongolicus seedlings exposed to HIPVs released from conspecific plants infested with larvae of Orgyia ericae were analyzed together with control and infested seedlings using nuclear magnetic resonance (NMR)-based metabolic technology and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Previous studies were used to assign peaks and chemical shift regions. 7,[17][18][19][20] We found that there was no significant change between the three spectra, but there was a difference in peak intensity in the unsaturated fatty acid region near 2 ppm and in the polyunsaturated fatty acid region near 2.8 ppm. When oak leaves are exposed to chemicals, the intensity of the peak is reduced in the aldehyde region of 8-12 ppm.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Previous studies were used to assign peaks and chemical shift regions. 7,[17][18][19][20] We found that there was no significant change between the three spectra, but there was a difference in peak intensity in the unsaturated fatty acid region near 2 ppm and in the polyunsaturated fatty acid region near 2.8 ppm. When oak leaves are exposed to chemicals, the intensity of the peak is reduced in the aldehyde region of 8-12 ppm.…”
Section: Resultsmentioning
confidence: 64%
“…Figure 1 shows the results of 1 H solution‐state NMR experiments on insoluble extracts of oak leaves. Previous studies were used to assign peaks and chemical shift regions 7,17–20 . We found that there was no significant change between the three spectra, but there was a difference in peak intensity in the unsaturated fatty acid region near 2 ppm and in the polyunsaturated fatty acid region near 2.8 ppm.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…After repeated lyophilization with D 2 O solution, the freeze-dried samples were dissolved in 0.5 mL of 99% D 2 O (Sigma) for NMR studies. 31 P-and 1 H-NMR spectroscopy were performed according to the reference with slight modification 41,42 . Briefly, for 31 P-NMR spectroscopy, the solution-state 31P NMR spectra were acquired at 24 °C using a JEOL ECA 600 spectrometer (JEOL Ltd., Japan) operating at 243 MHz with a 45° pulse width (5.2 µs pulse), an acquisition time of 0.77 s (50 ppm window centered at 0 ppm), a delay time of 2.0 s. The chemical shifts were determined in relation to external 85% H 3 PO 4 (at δ = 0).…”
Section: Artp Jet Instrumentationmentioning
confidence: 99%